Signaling Pathways and Sex Differential Processes in Autism Spectrum Disorder - Enriquez, Kristen D.; Gupta, Abha R.; Hoffman, Ellen J. (Frontiers in Psychiatry, 2021)
Autism spectrum disorders (ASDs) are a group of neurodevelopmental disorders associated with deficits in social communication and restrictive, repetitive patterns of behavior, that affect up to 1 in 54 children. ASDs clearly demonstrate a male bias, occurring approximately 4 times more frequently in males than females, though the basis for this male predominance is not well understood. In recent years, ASD risk gene discovery has accelerated, with many whole-exome sequencing studies identifying genes that converge on common pathways, such as neuronal communication and regulation of gene expression. ASD genetics studies have suggested that there may be a “female protective effect,” such that females may have a higher threshold for ASD risk, yet its etiology is not well understood. Here, we review common biological pathways implicated by ASD genetics studies as well as recent analyses of sex differential processes in ASD using imaging genomics, transcriptomics, and animal models. Additionally, we discuss recent investigations of ASD risk genes that have suggested a potential role for estrogens as modulators of biological pathways in ASD, and highlight relevant molecular and cellular pathways downstream of estrogen signaling as potential avenues for further investigation.